Stable Isotope Probing Techniques and Methodological Considerations Using 15N - Angel, Roey (Methods in molecular biology (Clifton, N.J.), 2019)
Nitrogen fixation and assimilation processes are vital to the functioning of any ecosystem. Nevertheless, studying these processes using 15N-based stable isotope probing was so far limited because of technical challenges related to the relative rarity of nitrogen in nucleic acids and proteins compared to carbon, and because of its absence in lipids. However, the recent adoption of high-throughput sequencing and statistical modelling methods to SIP studies increased the sensitivity of the method and enabled overcoming some of the challenges. This chapter describes in detail how to perform DNA- and RNA-SIP using 15N.
Keywords: bakterie fixující dusík; Isotope Labeling; bakteriální RNA; Nitrogen Isotopes; High-Throughput Nucleotide Sequencing; Nitrogen; izotopy dusíku; BNF; Diazotrophs; Amplicon sequencing; DNA-SIP; RNA-SIP; Centrifugation, Density Gradient; Nitrogen Fixation; DNA, Bacterial; DNA bakterií; izotopové značení; 15N; vysoce účinné nukleotidové sekvenování; centrifugace - gradient hustoty; fixace dusíku; Nitrogen-Fixing Bacteria; RNA, Bacterial